2015
DOI: 10.15448/1980-8623.2015.2.18250
|View full text |Cite
|
Sign up to set email alerts
|

Apoio Social e Comportamentos de Risco na Adolescência

Abstract: PsicoExceto onde especificado diferentemente, a matéria publicada neste periódico é licenciada sob forma de uma licença Creative Commons -Atribuição 4.0 Internacional. RESUMOO apoio social tem sido considerado fator de proteção ao engajamento de adolescentes em comportamentos de risco. Este estudo investigou a relação entre apoio social e comportamentos de risco (comportamentos sexual, infracional, suicida e uso de substâncias) em 374 adolescentes de Porto Alegre, entre 12 e 18 anos, de escolas públicas. Os in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
5
0
9
Order By: Relevance
“…The perception of social support from the family helps students to face the challenges and feel more accepted and more protected (Squassoni & Matsukura, 2014). The affective communication of the family assists students in socialization, in expanding the contact network and protects them from risk situations, such as friendships that con-tribute to risk behaviors (Alves & Dell'Aglio, 2015b;Olsson et al, 2016). Adolescents who have more contact and a good relationship with their parents are found to be happier and more satisfi ed with life (Tomé & Matos, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The perception of social support from the family helps students to face the challenges and feel more accepted and more protected (Squassoni & Matsukura, 2014). The affective communication of the family assists students in socialization, in expanding the contact network and protects them from risk situations, such as friendships that con-tribute to risk behaviors (Alves & Dell'Aglio, 2015b;Olsson et al, 2016). Adolescents who have more contact and a good relationship with their parents are found to be happier and more satisfi ed with life (Tomé & Matos, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Added to this, students have the same language and are in the same stage of development (in this case adolescence), which can facilitate the exchange of experiences (Tomé & Matos, 2012). Thus, it could be suggested that reciprocal friendly relationships contribute to good educational results of students in their daily lives (Wang & Holcombe, 2010), although some friendly relationships negatively affect the development of students with, for example, drug use, violence and aggressive behavior (Alves & Dell'Aglio, 2015b). Therefore, all the support networks are important to assist the development, because if one does not provide support, another can, so that the subject feels accepted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Um programa de habilidades sociais realizado por Leme et al (2016) com adolescentes em situação de vulnerabilidades social, evidenciou aumento na empatia, autocontrole, assertividade, abordagem afetiva, desenvoltura social e no escore total das habilidades sociais, bem como nos escores de autoeficácia e de apoio social dos professores. Nessa direção, tanto a percepção de apoio social (Alves & Dell'Aglio, 2015;Zappe & Dell'Aglio, 2016) quanto as crenças de autoeficácia (Valois et al, 2017;Zappe & Dell'Aglio, 2016) são fatores proteção e estão relacionadas a prevenção de condutas de risco ao ato infracional. Portanto, salienta-se a necessidade de se implementar intervenções que busquem promover essas variáveis em adolescentes em conflito com a lei.…”
Section: Introductionunclassified
“…3 Risk behavior has been associated with youth, as it is a phase of life that involves physical, emotional and social transformations permeated by the search for independence, autonomy and contact with new experiences, and can be considered as a period of greater vulnerability to risk. 4 Vulnerability can be seen more frequently as the number of semesters attended increases, which can be explained by the new phase that the young person is facing, being marked by the uncertainty of the future and possible beginning of the career path, which generates a high stress load. 5 Young people are an important group vulnerable to situations of exposure to risky behaviors.…”
Section: Introductionmentioning
confidence: 99%